Literatur Review : CRM Berujung pada Loyalitas Konsumen atau Kekecewaan - Prabowo, Theresya Amelia; Tarigan, Liyandri Rasbina (STIE Semarang, 2024)
Customer Relationship Management (CRM) has become an inseparable part of business processes. Without CRM, businesses cannot operate effectively. CRM is used to manage all interactions between companies and current and potential customers. Out of six research articles on CRM, five indicate a significant relationship between CRM and customer loyalty as well as the competitive advantage of companies, while the other article states that CRM does not have a significant relationship with the competitive advantage of companies. The method used in this research is a literature review from various electronic databases. This study is based on a review of various clinical articles and research published between 2011 and 2020. The results show that CRM has a significant impact on customer loyalty, but there is also a downside to CRM, namely the sense of injustice that can occur if the CRM programs implemented by the company are not properly targeted.